A NASICON‐typed Na4Mn0.5Fe0.5Al(PO4)3 cathode for low‐cost and high‐energy sodium‐ion batteries. Issue 1 (14th July 2022) - Liu, Xiao‐Hao; Lai, Wei‐Hong; Peng, Jian; Gao, Yun; Zhang, Hang; Yang, Zhuo; He, Xiang‐Xi; Hu, Zhe; Li, Li; Qiao, Yun; Wu, Ming‐Hong; Liu, Hua‐Kun
Abstract: Developing low‐cost and high‐voltage manganese (Mn)‐based Na superionic conductor (NASICON) cathode materials have attracted extensive interest. The low capacity and cycling instability of Na4 MnAl(PO4 )3 (NMAP), however, limits its performance in sodium‐ion batteries (SIBs). Herein, a binary Na4 Mn0.5 Fe0.5 Al(PO4 )3 (MNFAP) is fabricated to ease the structural instability and, in turn, deliver an improved reversible capacity of 102 mAh g −1 at 0.1 C and a high energy density of 287.7 Wh kg −1 . The synergistic interaction of Fe and Mn in Na4 Mn0.5 Fe0.5 Al(PO4 )3 /C composite leads to a one‐phase solid‐solution reaction mechanism with high structural reversibility. Theoretical calculations have also been performed to explain the upshifted voltage platform of both Fe 2+ /Fe 3+ and Mn 3+ /Mn 4+ redox potentials. The rational design of NASICON‐type cathodes by regulating their composition with dual metal ions provides new perspectives for developing high‐performance SIBs. Abstract : A comprehensive investigation of the structural and electrochemical properties of a binary Na superionic conductor‐structured material of Na4 Mn0.5 Fe0.5 Al(PO4 )3, and synergistic effects of Mn and Fe significantly enhance the energy density of Mn‐based polyanionic compounds.